مبانی مهندسی و روش های اجرایی سازه ای پدافند غیر عامل شریان حیاتی وزارت نیرو - حسین میسمی; پدرام موسوی (پدافند غیرعامل, 2010)
مبانی مهندسی و روش های اجرایی سازه ای پدافند غیر عامل شریان حیاتی وزارت نیرو